Research on the construction of the evaluation index system of game-based teaching - Wang, Yunhong; Zhang, Sujing; Hong, Hetiao (Frontiers in Psychology, 2023)
This research aims to combine the pursuit of literacy cultivation with a focused investigation into the evidence of game-based teaching (GBT). To achieve this, the study employs a mixed-methods approach including the interview method, Delphi method, and network hierarchical analysis (ANP) to analysis Expert opinions and construct a comprehensive GBT evaluation index system. The results indicated that a comprehensive GBT evaluation index system is comprised of five primary indicators: teaching objectives, game-based teaching methods, teaching content, game-based teaching processes, and game-based teaching characteristics. Additionally, there are 19 secondary indicators, such as objective content, game presentation, context construction, and flow experience. This study expects to effectively capture the unique attributes of game-based classes and to assist teachers in improving the design of GBT activities in practical applications.